Analytical and rheological studies of modified gel dosimeters exposed to X-ray beams - Romero, Marcelo Ricardo (2016)
The need to know the dose of X-rays to be applied to patients suffering diseases such as cancerrequires accurate and stable dosimetric devices. Currently, the use of gelatin-based dosimetershas yielded excellent results but lack adequate thermal stability. In this paper a chemicalmodification of the gelatin (at concentrations typically used for the preparation of dosimeters)using glutaraldehyde as a cross-linking agent is proposed. Through rheological studies it wasfound that modified gelatin with glutaraldehyde concentrations between 0.15 and 0.50 % w / vshow better thermal stability with an increase in elastic modulus of up to 100 times at 37°C andconvenient reaction times for the preparation of the dosimeters. Subsequently, a mathematicalmodel to easily predict the elastic modulus of materials prepared with different concentrationsof gelatin and glutaraldehyde was proposed. The analytical response of modified andunmodified materials was evaluated and no significant alteration of the dosimetric sensitivitywas found in the dosimeters (based on itaconic acid and N, N´-methylenebisacrylamide) whenan X-ray irradiation dose from 0 to 300 Gy was applied. It was found that the best thermal stability of dosimeters prepared with modified gelatin would decrease the loss of informationbetween the irradiation process and the absorbance reading, thereby improving the stability andlinear correlation of data.Overall, the results indicated that the dosimeters could be modified as proposed and achievesignificant improvements regarding to their thermal stability, without changing significantly theusual preparation process.